Allergic Fungal Sinusitis Causing Nasolacrimal Duct Obstruction. (April 2013) - Kim, Charles; Kacker, Ashutosh; Chee, Ru-Ik; Lelli, Gary J.
ABSTRACT Introduction: Allergic fungal sinusitis is thought to represent a chronic autoimmune reaction directed against fungal elements within the sinuses, and is commonly seen in individuals with a history of chronic sinusitis that is refractory to medical therapy. The authors present a case of allergic fungal sinusitis involving the lacrimal drainage system. Case: A 54-year-old woman initially presented with recurrent erythema and induration of the left nasolacrimal sac due to dacryocystitis, which was unresponsive to treatment with topical and systemic antibiotics. Radiological evaluation demonstrated the presence of multiple soft tissue masses along the medial canthi. During subsequent endoscopic dacryocystorhinostomy, significant amounts of allergic mucin were found within the sinuses and marked eosinophilia was present within tissue obtained from the lacrimal sac, findings highly suggestive of allergic fungal sinusitis. Conclusion: A diagnosis of allergic fungal sinusitis should be considered in patients presenting with epiphora in the appropriate clinical context. However, involvement of the lacrimal drainage system is an exceedingly unusual presentation.